An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show - Anggraini, Difta; Sudiran, Sudiran (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show